An effect of value co-creation on student benefits in COVID-19 pandemic. (20th November 2021) - Leem, Byung–Hak
The study is to propose a theoretical framework for a value co-creation process based on Service Dominant logic and to explore the effect of value co-creation on student benefits in a higher education environment. We applied value co-creation in an online education platform during the COVID-19 pandemic and conducted an empirical analysis on the value co-creation theory in higher education. We found the following results. First, co-production not only directly affects the value-in-use, but also affects student benefits, consisting of satisfaction and loyalty. Second, value-in-use also has a direct effect on student benefits and is more important than co-production in increasing student benefits in an online education platform. This study extends the Service Dominant logic theory by applying the Service Dominant logic, which has been widely studied in service marketing, to the higher education environment. This study also helps university stakeholders to understand the value of online education platform, understand the diversification of online education modalities, and understand the perspective of students as co-creator.